Bovine HOXA11 Gene Identified from RNA-Seq: mRNA Profile Analysis and Genetic Variation Detection Using ME Method and Their Associations with Carcass Traits - Yangming Huang; Kejing Zhang; Yafang Li; Sihuan Zhang; Zhanerke Akhatayeva; Fugui Jiang; Enliang Song; Xianyong Lan (Cells, 2023)
The Homeobox A11 (HOXA11) gene regulates limb skeletal development and muscle growth, thus, it was selected as a candidate gene for bovine carcass traits. In this study, we analyzed the mRNA expression level of HOXA11 in various tissues and cells, and determined the genetic variations in the HOXA11 gene, which might be used as molecular markers for cattle breeding. The mRNA expression profiles of HOXA11 in bovine different tissues showed that HOXA11 was highly expressed in both fat and muscle. The gene expression trend of HOXA11 in myoblasts and adipocytes indicated that HOXA11 might be involved in the differentiation of bovine myoblasts and adipocytes. The data in the Ensembl database showed that there are two putative insertion/deletion (InDel) polymorphisms in the bovine HOXA11 gene. The insertion site (rs515880802) was located in the upstream region (NC_037331.1: g. 68853364-68853365) and named as P1-Ins-4-bp, and the deletion site (rs517582703) was located in the intronic region (NC_037331.1: g. 68859510-68859517) and named as P2-Del-8-bp. These polymorphisms within the HOXA11 gene were identified and genotyped by PCR amplification, agarose gel electrophoresis and DNA sequencing in the 640 Shandong Black Cattle Genetic Resource (SDBCGR) population. Moreover, the mutation frequency was very low after detection, so the mathematical expectation (ME) method was used for detection. Statistical analysis demonstrated that P1-Ins-4-bp was significantly correlated with the beef shoulder (p = 0.012) and tongue root (p = 0.004). Meanwhile, P2-Del-8-bp displayed a significant correlation with the back tendon (p = 0.008), money tendon (p = 2.84 × 10-4), thick flank (p = 0.034), beef shin (p = 9.09 × 10-7), triangle thick flank (p = 0.04), triangle flank (p = 1.00 × 10-6), rump (p = 0.018) and small tenderloin (p = 0.043) in the female SDBCGR population. In summary, these outcomes may provide a new perspective for accelerating the molecular breeding of cattle through marker-assisted selection (MAS) strategies.